2000
DOI: 10.1046/j.1440-1746.2000.02080.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation of Helicobacter pylori‐positive and ‐negative functional dyspepsia

Abstract: The combination of retrosternal pain, weight loss, food intolerance and the absence of halitosis signified a 64% accuracy in predicting H. pylori infection. It is not possible to differentiate between H. pylori-positive and H. pylori-negative functional dyspeptics on the basis of clinical presentation and the number of complaints. However, overall symptom score and severity of several symptoms was significantly higher in the H. pylori-positive group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…According to organoleptic scoring, there was no clear relationship found between the gastric presence of H.pylori and halitosis. This result was in agreement with some other studies [47, 48, 59, 78]. However was not in agreement with the results of the studies conducted by Tiomny et al [49], Serin et al [50], Li et al [51], Katsinelos et al [79] and Chen et al [80].…”
Section: Discussionsupporting
confidence: 78%
“…According to organoleptic scoring, there was no clear relationship found between the gastric presence of H.pylori and halitosis. This result was in agreement with some other studies [47, 48, 59, 78]. However was not in agreement with the results of the studies conducted by Tiomny et al [49], Serin et al [50], Li et al [51], Katsinelos et al [79] and Chen et al [80].…”
Section: Discussionsupporting
confidence: 78%
“…19 Werdmuller et al have also shown that weight loss is significantly more common in the H. pylori infected patients. 20 On the other hand, Sarnelli et al demonstrated no difference in the clinical presentation of patients with or without H. pylori infection. 21 Recent reviews have highlighted the methodological problems in most of the therapeutic trials of anti-H. pylori treatment in patients with functional dyspepsia.…”
Section: Discussionmentioning
confidence: 98%
“…There is no 100% clear correlation found between these ulcers and halitosis. 50,51 In vitro studies show significant VSC production by H. pylori . 52 More recent research by Lee et al 53 confirmed this statement.…”
Section: Originmentioning
confidence: 99%